2017
DOI: 10.1021/acs.jpca.7b05194
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Phases of a S-Based Compound: Dimethyl Sulfide

Abstract: The high-pressure behavior of dimethyl sulfide was investigated at room temperature by Raman scattering measurements with pressures up to 30.1 GPa. Phase transitions at 1.3, 3.6-5.8, and 17.2 GPa were found and evidenced by the frequency shifts, pressure coefficients, and changes in fwhm of related modes. These phase transitions were suggested to result from the changes in the inter- and intramolecular bonding of the material. Interestingly, the CH groups was compelled to be frozen in positions at a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…With further increasing pressure up to 40.6 GPa, Mode ν 2 seems to become “fat” quickly, which suggests that DMSe starts to solidify by compression . Compared to the (CH 3 ) 2 S at high pressure, C–Se stretch modes in this region behave very humble, and reversal change in both modes as a result of Fermi resonance is not found, which is evidence for the stable symmetry assignment in this crystal phase.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…With further increasing pressure up to 40.6 GPa, Mode ν 2 seems to become “fat” quickly, which suggests that DMSe starts to solidify by compression . Compared to the (CH 3 ) 2 S at high pressure, C–Se stretch modes in this region behave very humble, and reversal change in both modes as a result of Fermi resonance is not found, which is evidence for the stable symmetry assignment in this crystal phase.…”
Section: Resultsmentioning
confidence: 81%
“…This provides further evidence for the solid–solid phase transition at this pressure. Additionally, it is found that the peaks of Modes ν 7 and ν 8 maintain stable, only broadened and weakened, and Mode ν 8 nearly vanishes with pressure up to 40.6 GPa, which is totally different from the (CH 3 ) 2 S at this region …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations